Reorganisation of faecal microbiota transplant services during the COVID-19 pandemic. Issue 9 (3rd July 2020) - Ianiro, Gianluca; Mullish, Benjamin H; Kelly, Colleen R; Kassam, Zain; Kuijper, Ed J; Ng, Siew C; Iqbal, Tariq H; Allegretti, Jessica R; Bibbò, Stefano; Sokol, Harry; Zhang, Faming; Fischer, Monika; et al.
Abstract : The COVID-19 pandemic has led to an exponential increase in SARS-CoV-2 infections and associated deaths, and represents a significant challenge to healthcare professionals and facilities. Individual countries have taken several prevention and containment actions to control the spread of infection, including measures to guarantee safety of both healthcare professionals and patients who are at increased risk of infection from COVID-19. Faecal microbiota transplantation (FMT) has a well-established role in the treatment of Clostridioides difficile infection. In the time of the pandemic, FMT centres and stool banks are required to adopt a workflow that continues to ensure reliable patient access to FMT while maintaining safety and quality of procedures. In this position paper, based on the best available evidence, worldwide FMT experts provide guidance on issues relating to the impact of COVID-19 on FMT, including patient selection, donor recruitment and selection, stool manufacturing, FMT procedures, patient follow-up and research activities.